Impact of Transnational Crimes on Vulnerabilities of Pakistan’s Image - Fahad, Hameed Khan (2024)
For several decades, academic discussions have raged over how to properly define the term "Transnational Organized Crime." As far back as the 1970s, Reuter and Rubinstein warned that identifying Transnational Organized Crime (TOC) will always be the achilles’ heel of investigations looking into criminal cross-border conduct. In recent years, numerous new laws have been enacted to affirm drug and human trafficking, money laundering, insider trading, and corruption all unlawful. Since it encompasses so many activities, different actors, agent provocateurs and more than one country; transnational organized crime is a difficult subject to handle. TOC generates between $1.6 to $2.2 trillion per year and thus considered as a danger to international security due to its "explosive and destabilizing repercussions" potential. TOC poses a significant threat to both direct and indirect peace, as well as cultural peace. It jeopardizes human rights, world peace, and the Sustainable Development Goals (SDG). The industry of transnational organized crime is one that is always adapting to new markets and developing new types of criminal activity. It is an illicit enterprise that cuts across all boundaries; cultural, social, linguistic, and geographic. This corporation does not recognize any borders or standards because it operates outside of them. Apropos to the premise that TOC is more destructive than conventional and traditional crimes, it is added that each country has it’s own dynamics, causes and vulnerabilities to deal with Transnational Organized Crimes. Similarly, Pakistan faces special challenges in determining their causes, devising effective preventive tactics and instituting appropriate adjudication procedure. This investigation examines three types of TOC in Pakistan: traditional; which primarily involves illegal commodity (drug) trafficking and racketeering, economic; which includes money laundering and social; which includes human trafficking. Academics and researchers are unable to convey knowledge about TOC because it is covert and hidden, and because it is related to elites. As globalization have grown in popularity, TOC has proliferated in Pakistan. This means that even "domestic" gangs are becoming more involved in cross-border crimes and that all of the main criminal organizations now work and are organized on a global basis. This is serious threat to Pakistan’s economy, its image and reputation in globalized world.The goal of this research is to fill in the gaps that have been detected in the existing knowledge. People will better understand why the rates of international crime in developed countries and Pakistan are so drastically different as a direct result of this study's findings.